Endoscopic third ventriculostomy - experience of 16 cases (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: endoscopic third ventriculostomy; obstructive hydrocephalusdoi: 10.3329/jcmcta.v19i2.3867Journal of Chittagong Medical College Teachers' Association 2008: 19(2):27-32